Analisis Setengah Menganggur (Underemployment) Di Provinsi Sumatera Barat: Determinan Dan Implikasi - Dewi Zaini Putri; Melti Roza Adry (Universitas Negeri Padang, 2018)
This research have purposes to analysis impact of demographic and economic factors that influence underemployment in Sumatera Barat. Using data Sakernas 2015 to analyze impact of demographic and economic factors to underemployment we use multinomial logit. This model will produce determinant of underemplyment in Sumatera Barat. Based on result we can conclude that demographic factors ( sex, age, education, dan region) and economic factors ( total of wage, occupation, and job status) as a simultant have significant effect to underemployment in Sumatera Barat with probability 0,000 < α = 0,05. While in partial demographic factors ( sex, age, and region) and economic factors ( total of wage, occupation, and job status) have significant effect to underemployment in Sumatera Barat.